2003
DOI: 10.1152/ajpgi.00428.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonicity-induced increases in duodenal mucosal permeability facilitates adjustment of luminal osmolality

Abstract: The integrated response to hypotonic NaCl solutions (100, 50, 25, and 0 mM NaCl) in proximal duodenum of anesthetized rats was examined. Luminal alkalinization, fluid flux, duodenal contractions, blood-to-lumen clearance of 51Cr-labeled EDTA (mucosal permeability), and perfusate osmolality were studied in the absence and presence of the cyclooxygenase inhibitor indomethacin. In response to hypotonic solutions net fluid absorption, increases in permeability and perfusate osmolality were markedly higher in indom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 28 publications
5
46
0
Order By: Relevance
“…Furthermore, it has previously been shown that nicotinic receptor blockade almost abolish the hypotonicity-induced increase in mucosal permeability (32) but not that induced by acid or ethanol as shown in the present study (15). These data suggest that the increase in duodenal epithelial permeability in response to ethanol, acid, or hypotonicity is mediated by different mechanisms supporting the notion of physiological regulation of duodenal epithelial paracellular permeability.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, it has previously been shown that nicotinic receptor blockade almost abolish the hypotonicity-induced increase in mucosal permeability (32) but not that induced by acid or ethanol as shown in the present study (15). These data suggest that the increase in duodenal epithelial permeability in response to ethanol, acid, or hypotonicity is mediated by different mechanisms supporting the notion of physiological regulation of duodenal epithelial paracellular permeability.…”
Section: Discussionsupporting
confidence: 86%
“…Another positive action of COX inhibition is the increase in mucosal 'protective' bicarbonate secretion, an effect most probably coupled to the induction of duodenal motility (Sababi & Nylander 1994, Sababi et al 1996, Nylander et al 2001. This effect in turn may be coupled to the increase in mucosal permeability and net fluid absorption seen after COX-inhibition (Nylander et al 2003). This effect in turn may be coupled to the increase in mucosal permeability and net fluid absorption seen after COX-inhibition (Nylander et al 2003).…”
Section: Figurementioning
confidence: 99%
“…Interestingly, perfusion of the duodenum with hypotonic solutions increases the bloodto-lumen clearance of 51 Cr-EDTA, a reliable probe for assessment of paracellular permeability in vivo (Nylander & Hä llgren 1998), in an osmolality-dependent manner, i.e. The physiological function of the hypotonicityinduced increase in permeability may be to 'boost' the transfer of osmolytes, mainly NaCl, into the lumen thereby facilitating the adjustment of luminal osmolality (Nylander et al 2003). Furthermore, there exists a strong positive linear correlation between the increase in mucosal permeability and the rise in luminal osmolality.…”
mentioning
confidence: 99%